White Nationalist Rhetoric, Neoliberal Multiculturalism and Colour Blind Racism: Decolonial Critique of Richard Spencer’s Campus Visit - Ramasubramanian, Srividya; Miles, Caitlin (Javnost-The Public, 2018)
This essay examines white nationalist discourses within the U.S. context of the alt-right movement from a decolonial perspective. It challenges concepts grounded in the enlightenment era that connect whiteness and European identity with civilisation and progress, thereby positioning whiteness as a disciplinary discourse. Specifically, our essay will use the hateful rhetoric of Richard Spencer, who is credited with coining the term alt-right movement, and analyze the white nationalist rhetoric surrounding his visit to Texas A&M University as a case study. It examines the fallacy and violence of white supremacist rhetoric that constructs Europe and North America as a “white” space, thus symbolically and politically erasing complex indigenous histories and peoples. It investigates how diversity, inclusion and multiculturalism are utilised to normalise discourses of white supremacy within historically white institutions. This type of multiculturalism serves as a form of colourblind racism that reinforces rather than challenges white supremacy. Specifically, it examines the University’s response to Spencer’s visit by hosting the Aggies United entertainment performance emphasising unity as an expression of neoliberal multiculturalism, which is contrasted with critical anti-racist pedagogy and other more meaningful forms of resistance such as protests.